The impact of syncope during clinical presentation of sustained ventricular tachycardia on total and cardiac mortality in patients with chronic Chagasic heart disease - Leite,Luiz Roberto (2001)
OBJECTIVE: To assess the impact of syncope during sustained ventricular tachycardia on total and cardiac mortality in patients with chronic chagasic heart disease. METHODS: We assessed 78 patients with sustained ventricular tachycardia and chronic Chagas' heart disease. The mean age was 53±10 years, 45 were males, and the mean ejection fraction was 49.6±13%. The patients were divided into 2 groups according to the presence (GI=45) or absence (GII=33) of syncope during sustained ventricular tachycardia. RESULTS: After a mean follow-up of 49 months, total mortality was 35% (28 deaths), 22 deaths having a cardiac cause (78.6%). No difference was observed in total (33.3% x 39.4%) and cardiac (26.7% x 30.3%) mortality, or in nonfatal sustained ventricular tachycardia between GI and GII patients (57.6% x 54.4%, respectively). However, the presence of syncope during recurrences was significantly greater in those patients who had had the symptom from the beginning (65.4% x 18.1%, p<0.01). CONCLUSION: Syncope during the presentation of sustained ventricular tachycardia is not associated with an increase in total or cardiac mortality in patients with chronic Chagas' heart disease. However, syncope during the recurrence ventricular tachycardia is greater in patients experiencing syncope in the first episode, of sustained ventricular tachycardia.